A novel heat transfer enhancement technique for performance improvements in encapsulated latent heat storage system. (April 2018) - Niyas, Hakeem; Muthukumar, P.
Highlights: Proposed a novel encapsulation technique for enhanced storage/discharge rate. Developed a numerical tool for comparing the basic and encapsulated LHS system. Effective heat capacity method is used for incorporating the latent heat of PCM. Novel capsule offers a reduction of 48.4/63.9% in the charging/discharging time. Commercial viability of the novel concept is also explored. Abstract: Latent heat storage (LHS) using phase change materials (PCMs) in the form of encapsulated capsules are recently used in steam accumulators for reducing the pressure drop during the discharge of steam. Due to high thermal resistance offered by the PCM in capsules with a larger diameter, more number of smaller diameter capsules need to be used for meeting the required storage capacity. In the present study, a novel heat-transfer enhancement technique consists of tube-in-tube LHS system with a very small inner tube is proposed for effective heat transfer in cylindrical LHS capsules. With this technique, less number of capsules can yield the similar or higher storage capacity in a comparatively lesser charging/discharging time. A numerical model is developed to study the performance characteristics of the proposed novel heat-transfer enhancement technique. For comparing the performance characteristics of the basic and the proposed novel heat-transfer enhancement technique, capsules having a LHS capacity of 0.5 MJ are considered. Sodium nitrate and SS304 are selected as the PCM and encapsulating material. In the numerical model, the effective heat capacity method is applied to consider the latent heat of the PCM and Boussinesq approximation is used to include the natural convection of the molten layer of the PCM. Numerically predicted melt fraction values during the charging process match well the experimental data reported in the literature. Various storage performance parameters such as charging/discharging time, energy storage/discharge rate and melt fraction are evaluated for basic/novel capsule and a comparison is made between them. For the given operating conditions, basic/novel LHS capsule complete the charging and discharging processes around 64/33 min and 158/57 min, respectively. A commercial viability study is also done on the proposed novel concept and the results showed that the novel LHS capsule has promising features for commercialization.